CRIPTO promotes an aggressive tumour phenotype and resistance to treatment in hepatocellular carcinoma. Issue 3 (9th May 2018) - Karkampouna, Sofia; van der Helm, Danny; Gray, Peter C; Chen, Lanpeng; Klima, Irena; Grosjean, Joël; Burgmans, Mark C; Farina‐Sarasqueta, Arantza; Snaar‐Jagalska, Ewa B; Stroka, Deborah M; Terracciano, Luigi; van Hoek, Bart; et al.
Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer‐related death worldwide. Despite increasing treatment options for this disease, prognosis remains poor. CRIPTO (TDGF1) protein is expressed at high levels in several human tumours and promotes oncogenic phenotype. Its expression has been correlated to poor prognosis in HCC. In this study, we aimed to elucidate the basis for the effects of CRIPTO in HCC. We investigated CRIPTO expression levels in three cohorts of clinical cirrhotic and HCC specimens. We addressed the role of CRIPTO in hepatic tumourigenesis using Cre‐ loxP ‐controlled lentiviral vectors expressing CRIPTO in cell line‐derived xenografts. Responses to standard treatments (sorafenib, doxorubicin) were assessed directly on xenograft‐derived ex vivo tumour slices. CRIPTO‐overexpressing patient‐derived xenografts were established and used for ex vivo drug response assays. The effects of sorafenib and doxorubicin treatment in combination with a CRIPTO pathway inhibitor were tested in ex vivo cultures of xenograft models and 3D cultures. CRIPTO protein was found highly expressed in human cirrhosis and hepatocellular carcinoma specimens but not in those of healthy participants. Stable overexpression of CRIPTO in human HepG2 cells caused epithelial‐to‐mesenchymal transition, increased expression of cancer stem cell markers, and enhanced cell proliferation and migration. HepG2‐CRIPTO cells formed tumours when injected into immune‐compromised mice, whereas HepG2 cells lacking stable CRIPTO overexpression did not. High‐level CRIPTO expression in xenograft models was associated with resistance to sorafenib, which could be modulated using a CRIPTO pathway inhibitor in ex vivo tumour slices. Our data suggest that a subgroup of CRIPTO‐expressing HCC patients may benefit from a combinatorial treatment scheme and that sorafenib resistance may be circumvented by inhibition of the CRIPTO pathway. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.